EXPRESSION OF MENTAL STATE IN YOLDOSH ESHBEK'S POETRY (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article analyzes the degree of realization of feeling, the artistic-aesthetic nature of perception intuition at the level of poetic worldview. It talks about the presentation of the lyrical subject, the attitude to the object of the poetic image, the integrity of the mood and mental state in the text, the conflict between consciousness and artistic observation, and the improvement of the narrative technique. Although the personality of the poet and the nature of the philosophical goal are actually alternative concepts to each other, the poetic harmony of coincidence characterizes the art of words.